Reconstruction of the Sigma0 baryon in Ag+Ag collisions at sqrt(s_NN) =2.55 GeV with HADES - Becker, Marten; Justus Liebig University Giessen (My University, 2025)
This work presents the experimental reconstruction of the Sigma0 baryon in – with respect to NN interactions – subthreshold Ag+Ag collisions at 1.58 AGeV kinetic beam energy measured with the HADES experiment. At the HADES experiment, which is located at GSI in Darmstadt, Germany, heavy ion collisions at moderate freeze-out temperatures and high baryon chemical potential are measured, analyzed, and evaluated in comparison with the existing data as well as theoretical predictions. This kinetic beam energy corresponds to a center of mass energy of sqrt(s_NN) = 2.55 GeV, which is the Lambda baryon production threshold in NN collisions. With only a small mass difference of Sigma0 to the Lambda baryon of 77 MeV/c^2, Sigma and Lambda baryons are the lightest strangeness containing baryons. Since all quantum numbers of the Sigma0 and the Lambda baryon are identical, their production mechanisms are expected to be very similar. Due to a different spin configuration of the valence quarks inside the Sigma0 , the Sigma0 is slightly more heavy and decays with nearly 100 % branching ratio into Lambda-photon. However, the reconstruction of the low-energy photon is challenging for most detectors, particularly when attempting to concurrently satisfy the requirements of Lambda reconstruction. For the beamtime of the analyzed Ag+Ag collisions, 15 billion events were recorded. The newly installed electromagnetic calorimeter enables photon reconstruction for HADES for the first time without relying on the previously used conversion method. Within the 0-40 % most central events, around 8000 Sigma0 baryons were reconstructed in the Lambda-photon channel with a significance of approximately 10. In addition to the newly installed electromagnetic calorimeter, the RICH was upgraded with newmulti-anode photomultipliers which strongly enhance reconstruction efficiency as well as lepton purity. These advantages were used for feasibility studies in the Lambda-e+e− decay channel. Hints for a signal were found that are consistent with the extracted signal from the Lambda-photon channel, but due to the small statistics, only a significance level of less than 3 was achieved. A full efficiency and acceptance correction was performed with a resulting multiplicity of 0.014 ± 0.002stat. ± 0.004sys. produced Sigma0 per event which corresponds to a Lambda/Sigma0 ratio at freeze-out of 3.2 ± 0.3stat. ± 0.6sys.. This represents the first measurement of this ratio for a subthreshold Sigma0 production in nucleus nucleus collisions. Comparing to the available world data of p+p collisions close to the Sigma0 production threshold, this ratio increases in p+p to values of 30 and higher. Even more, the measured ratio compares well to measurements in p+p far from threshold. This indicates that the NN threshold has no influence on the Sigma0 production for this energy. The Lambda-photon channel result is compared to statistical hadronization model fit as well as to several transport model predictions. The statistical model calculations are in good agreement to our measurement which endorses the possibility of hyperon production in a thermally equilibrated medium. In this case, the freezeout ratio is directly connected to the mass difference of two states with the same quantum numbers, resulting in a temperature estimation of the created matter by only measuring Lambda and Sigma0. From these measurements T=66 MeV is extracted, which compares well with fits of all hadrons with a statistical model.
Keywords: ddc:530